A persona rapper de Criolo inscrita em canções de Nó na Orelha - Zoteli, Wallas Gomes (2016)
Criolo author refers to himself, with recurrence, as rapper/MC; it is the nickname, among others pegged to his public persona, that best retrieves and highlights his role in the São Paulo rap scene. He founded Rinha dos MCs, acted in film production Profissão MC (2009), has launched an independent album of rap songs Ainda Há Tempo (2006); and punctuate these facts by way example. However, when released the Nó na Orelha album (2011), which is heard in the songs is a careful work with melodies and dictions identified with other musical genres than the rap, and it is said with greater emphasis on five of ten tracks available there; on them, we intend to investigate how the rap is inscribed and how the rapper title remains and updates. Articulated, as a basic theoretical, conceptual contributions of Paul Zumthor (1993; 2010; 2014), Ruth Finnegan (2008), Simon Frith (1996), among others. Assume the word sung as performance studies object, which in turn becomes liable to interest in literary studies; thus, according to zumthorian approach, it is understood song in the comprehensive spectrum of oral poetry, it is treated as a work and performance in auditory means, in its complex articulation in the triad text-musicperformance, without forgetting the voice and gender recognition these intricacies. It is the scope of this paper to argue that persona - concept anchored in Carl Jung (1981) and Marcel Mauss (2003) – rapper of Criolo is inscribed not only on five rap songs, but also on the other five in appearance less identified with this genre. Therefore, the corpus collected from the hearing of the album in question, focuses on five works recognized here as "non-rap songs": “Bogotá”; “Não Existe Amor em SP”; “Freguês da Meia-noite”; “Samba Sambei”; “Linha de Frente”. On them, we try to emphasize the performative elements within the sung word, which mark the entry of the persona/attitude rapper to other musical aesthetics. We compare punctually the corpus in focus to works by other cancionistas representatives of various musical styles and genres to develop more compelling clarifications to reinforce interpretive statements registered in each of the presented readings.